The E LiBANS project: Thermal and epithermal neutron sources based on a medical Linac. (December 2020) - Monti, V.; Costa, M.; Durisi, E.; Ferrero, M.; Menzio, L.; Sans-Planell, O.; Visca, L.; Bedogni, R.; Treccani, M.; Alikaniotis, K.; Giannini, G.
Abstract: The E_LIBANS project (INFN) aims at producing neutron facilities for interdisciplinary irradiation purposes among which pre-clinical research for BNCT. After the successful setting-up of the thermal neutron source based on a medical LINAC, a similar apparatus for epithermal neutrons has been developed. Both structures are based on an Elekta 18 MV coupled with a photoconverter-moderator system which deploys the (γ, n) reaction to convert the X-rays into neutrons. This communication describes the two neutron sources and the results obtained in their characterization. Highlights: Development of photonuclear thermal and epithermal neutron sources for samples irradiation. Sources based on an 18 MV medical-type electron LINAC and a photoconverter assembly. Homogeneous thermal or epithermal neutron fields obtained in closed experimental cavities. Active Bonner Sphere System used for the neutron spectrum measurement in the cavities. Field characterization and feasibility demonstration of reduced-cost photonuclear neutron sources.